Biomaterial-Mediated Modification of the Local Inflammatory Environment - Browne, Shane; Pandit, Abhay (Frontiers in Bioengineering and Biotechnology, 2015)
Inflammation plays a major role in the rejection of biomaterial implants. In addition, despite playing an important role in the early stages of wound healing, dysregulated inflammation has a negative impact on the wound healing processes. Thus, strategies to modulate excessive inflammation are needed. Through the use of biomaterials to control the release of anti-inflammatory therapeutics, increased control over inflammation is possible in a range of pathological conditions. However, the choice of biomaterial (natural or synthetic), and the form it takes (solid, hydrogel or micro-/nanoparticle) is dependent on both the cause and tissue location of inflammation. These considerations also influence the nature of the anti-inflammatory therapeutic that is incorporated into the biomaterial to be delivered. In this report, the range of biomaterials and anti-inflammatory therapeutics that have been combined will be discussed, as well as the functional benefit observed. Furthermore, we point towards future strategies in the field that will bring more efficacious anti-inflammatory therapeutics closer to realization.